A potência política dos territórios periféricos na metrópole de São Paulo. - do Amaral e Silva, Fabiana Felix; de Oliveira, Dennis (Polisemia)
The aim of this reflection paper is to contribute to the discussion on Latin American social movements. It deals with the new territorialities built on everyday struggles and fights of social movements of the periphery in the metropolis of São Paulo. The territory is assumed as a space of conflict and construction of meanings out of contradictions in the perspectives of local social movements and the interests of hegemonic segments. The legitimacy of these movements' struggles lies on the break-up with oppression and expropriation processes, our territorial and community links; the identitary, political, and critical consolidation of their roots, the strengthening of their communicative processes, and the production of a knowledge of their own, which brings up the discussion of the political potential of peripheral territories.